PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS XII IPS SMAN 1 ULAKAN TAPAKIS - Sikumbang, Indra Saputra (Jurnal Edukasi dan Penelitian Matematika, 2024)
Students must grasp mathematical principles. However, class XII IPS SMAN 1 Ulakan Tapakis kids still struggle with maths. Numbered Heads Together (NHT) is used to solve this problem. This study described the development of mathematical concept understanding of class XII IPS SMAN 1 Ulakan Tapakis students during NHT model application and analysed whether NHT model learning is better than direct learning. Quasi experimental research with non-equivalent posttest-only control group design and descriptive study are used. In 2023/2024, SMAN 1 Ulakan Tapakis XII social studies students were the study population. Simple random sampling was used. Quizzes and final maths tests were used for research. H0 is rejected based on hypothesis testing results with a real level of 0.05 (P-value = 0.044). Thus, the NHT model affects class XII IPS SMAN 1 Ulakan Tapakis pupils' mathematics knowledge.Keywords– Numbered heads together model, Understanding Mathematical Concepts, Direct Learning.